Phacodonesis in Angle-Closure Glaucoma: Phacomorphic or Other Lens- Induced? Poster Presentation - Case Report - General practitioner - Claudia, Alyssa; Caesaria, Aquirina; Noerdiyani, Niken Indah; Koesoemowardani, Dianawati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Glaucoma is defined as progressive optic neuropathies characterized by optic disk cupping, reduced visual field, and visual loss. As a “silent thief of sight”, glaucoma ranked second worldwide and third in Indonesia as the cause of blindness. The cause of glaucoma varies, one of which is lens-induced which presents as loss of vision and red eye. Case Illustration : A 53-year-old female complained about blurred and pained red eyes. Examination of the right eye revealed VOD 1/300, cloudy-milky lens, phacodonesis, and IOP 26.3 mmHg. She was diagnosed with angle-closure glaucoma suspected as phacomorphic or other lens-induced and was treated by topical hypotensive agents and phacoemulsification with IOL implantation procedure. Right eye examination on day one post operation showed VA 2/60 and IOP 13.6 mmHg. Improvement on two weeks follow- up revealed VA 6/15 with best VA of 6/6, IOP 15.7 mmHg, CD ratio 0.5, and negative glaucoma optic neuropathy (GON) finding. Discussion : When accompanied by phacodonesis, angle-closure glaucoma is mainly caused by a secondary process. It involves zonule of Zinn fragility, which usually occurs in subluxation but also appear in hypermature cataract. Dilated eye examination showed no sign of subluxation, therefore the final diagnosis was phacomorphic glaucoma and hypermature cataract. Cataract surgery as the definitive treatment must be done at an appropriate time as was done for this patient with a favorable outcome. Conclusion : The presence of phacodonesis in angle-closure glaucoma should be thoroughly evaluated. Meticulous decisions on definitive treatment can be planned afterward.